Retail Management, Global Edition - Berman, Barry R.; Evans, Joel R.; Chatterjee, Patrali M. (Pearson International Content, 2017)
For courses in Retail Management. A contemporary text that helps students thrive in today’s retailing industry Retail Management: A Strategic Approach is built on the fundamental principle that retailers have to plan for and adapt to a complex, changing environment. Without a pre-defined and well-integrated strategy, retailers may flounder and be unable to cope with the environment that surrounds them. This text helps readers become good retail planners and decision makers. The 13th Edition incorporates updated data that reflects the current world economic climate, extensive coverage of omnichannel retailing, and many new vignettes, questions, and cases, so that students can thrive in today’s retailing industry. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.